2021
DOI: 10.1080/0886022x.2021.1914655
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus versus cyclophosphamide for patients with idiopathic membranous nephropathy and treated with steroids: a systematic review and meta-analysis of randomized controlled trials

Abstract: 2021) Tacrolimus versus cyclophosphamide for patients with idiopathic membranous nephropathy and treated with steroids: a systematic review and meta-analysis of randomized controlled trials,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…In the meantime, we are attracted by an interesting phenomenon that TAC assumes an important role among the treatments in the significant effect group (TAC, TAC + MMF, and RIT). In terms of TR and 24-h UTP, TAC always presented significantly higher probabilities of being in a dominant position, which was the same as what Huang et al (2021 ) and Zhu et al (2017 ) conducted. Meta-analyses ( Zhu et al, 2017 ) also demonstrate that TAC has superior short-term efficacy and higher safety than CTX within 1 year, but the long-term effects need to be confirmed through further RCTs.…”
Section: Discussionsupporting
confidence: 81%
“…In the meantime, we are attracted by an interesting phenomenon that TAC assumes an important role among the treatments in the significant effect group (TAC, TAC + MMF, and RIT). In terms of TR and 24-h UTP, TAC always presented significantly higher probabilities of being in a dominant position, which was the same as what Huang et al (2021 ) and Zhu et al (2017 ) conducted. Meta-analyses ( Zhu et al, 2017 ) also demonstrate that TAC has superior short-term efficacy and higher safety than CTX within 1 year, but the long-term effects need to be confirmed through further RCTs.…”
Section: Discussionsupporting
confidence: 81%
“…Instead of utilizing a small dose of glucocorticoids or cyclophosphamide, we chose losartan potassium and tacrolimus to control the progression of kidney injury. Tacrolimus, a calcineurin inhibitor, could combine with immune avidin and suppress cytoplasm calcineurin activity, subsequently blocking the T cell proliferation and avoiding bone marrow suppression[ 7 ]. Studies have shown that calcineurin inhibitors have effects on the podocyte cytoskeleton, resulting in a non-specific reduction of proteinuria[ 8 ].…”
Section: Discussionmentioning
confidence: 99%